Managing The Impact of Decreased in Quantity, Quality of Groundwater, and Increased Domestic Waste Due To The Ready-Mix Concreate Industry: Pengelolaan Dampak Penurunan Kuantitas, Kualitas Air Tanah, dan Peningkatan Sampah Domestik Akibat Industri Beton Ready-Mix - Izzah, Kuni Zukhrufal; Putro, Raden Kokoh Haryo; Purnama, Elanda Reinelda (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Ready-Mix Concrete Industry located in Kediri Regency is preparing UKL-UPL documents to meet the requirements of the Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management through the Kediri Regency Environmental Agency. This study was conducted using the observation method on the impact sources of operational activities, utilizing secondary data from the industry's UKL-UPL documents. The impact caused includes a decrease in the quantity and quality of groundwater due to the fulfillment of industrial clean water needs amounting to 4,570 m³/day for domestic needs and 145 m³/day for other supporting activities sourced from groundwater, with wastewater generation amounting to 3,656 m³/day. Also, the waste generated amounts to 21.7 kg/day, which impacts the increase in domestic waste. Management efforts will be carried out in the form of processing and utilizing the generated waste in accordance with quality standards and regulations in force, with regular monitoring conducted in collaboration with laboratories and relevant ministries. This study can be used as a guideline for the community in preserving the environment and as a representation of policies in the Kediri Regency area.